The right to protection of employee’s personal data - Лагутіна Ірина Вікторівна; Лагутина Ирина Викторовна; Lagutina Irina V. (My University, 2014)
The article examines the main approaches to the definition of personal data of employees, the role of protection which in modern socio-economic environment significantly increases. Defines the general requirements for the processing and protection of personal data. Emphasized the need for consolidation in the national legislation the right of employees to protection of personal data and guarantee its implementation.

У статті аналізуються основні підходи до визначення персональних даних працівників, роль захисту яких в сучасних соціально-економічних умовах значно зростає. Визначаються загальні вимоги до обробки і захисту персональних даних працівників. Підкреслюється необхідність закріплення в національному законодавстві права працівників на захист персональних даних і гарантій його реалізації.

В статье анализируются основные подходы к определению персональных данных работников, роль защиты которых в современных социально-экономических условиях значительно возрастает. Определяются общие требования к обработке и защите персональных данных работников. Подчеркивается необходимость закрепления в национальном законодательстве права работников на защиту персональных данных и гарантий его реализации.
Lagutina I. V. The right to protection of employee’s personal data / I. V. Lagutina // Юридичний вісник. – 2014. – № 3. – С. 215-220.
Keywords: human rights; personal data of employees; processing of personal data of employees; use of personal data of employees; права людини; особисті дані співробітників; обробка персональних даних працівників; використання персональних даних працівників; права человека; личные данные сотрудников; обработка персональных данных работников; использование персональных данных работников